Psychological preparation of goalkeepers for the 11-m penalty kick in soccer - A review - Lidor, R.; Ziv, G.; Gershon, T. (The Sport Psychologist, 2012)
In this article we reviewed a series of studies (n = 18) on psychological preparation of the goalkeeper (GK) for the 11-m penalty kick in soccer. The main findings of this review were that deception strategies (e.g., standing slightly off-center) can increase the chances of the kick being directed to a desired direction, and that individual differences among GKs should be considered when planning sport psychology programs for GKs. A number of research limitations and methodological concerns, such as the lack of ecological validity of the tasks performed in the studies and the lack of studies on psychological interventions, were discussed. In addition, a number of practical implications for sport psychology consultants who work with GKs in soccer were suggested.